Robot-assisted exercise improves gait and physical function in older adults: a usability study - Su-Hyun Lee; Eunmi Kim; Jinuk Kim; Hwang-Jae Lee; Yun-Hee Kim (BMC Geriatrics)
Abstract Background With increasing age, individuals are more likely to experience physical disabilities, functional declines, and mobility limitations. Wearable robots or exoskeletons are relatively new technologies that can help address these issues, reduce healthcare costs, and support home healthcare, decreasing the burden of chronic disease. The purpose of this study was to investigate the usability of Bot Fit after task-specific physical activities and functional gait training, as well as to examine the effects of a wearable hip exoskeleton, Bot Fit, on gait, physical function, and muscle strength in older adults living in residential care facilities. Methods A total of 32 older adults living in residential care facilities were included in this uncontrolled study. All participants performed eight weeks of task-specific physical activities and functional gait training using Bot Fit, with three exercise sessions per week (24 sessions in total). They were assessed at three time points: pre-test (baseline, T0), mid-test (after the 12 exercise sessions, T1), and post-test (after the last exercise session, T2). Each assessment evaluated functional outcomes (10-m walk test [10MWT], timed up-and-go [TUG], 6-min walk test [6MWT], Berg balance scale [BBS], four-square step test [FSST], and geriatric depression scale-short form [GDS-SF]), as well as muscle strength of the lower extremities. After the post-test, the participants completed a questionnaire to evaluate Bot Fit usability. Results A significant improvement was observed in all physical assessments, including the 10MWT, TUG, 6MWT, BBS, and FSST, from T0 to T2. It is noteworthy that 10MWT, TUG, and BBS also changed significantly from T0 to T1 and from T1 to T2. Muscle strength in hip flexion, hip extension, knee flexion, knee extension, ankle dorsiflexion, and ankle plantar flexion all improved significantly from T0 to T2, with knee flexion, knee extension, ankle dorsiflexion, and ankle plantar flexion showing significant improvements at all time points. Additionally, on the usability questionnaire, most participants provided positive feedback about their experience with Bot Fit. Conclusion The findings of this study suggest that task-specific physical activity and functional gait training with Bot Fit have several key advantages for improving gait, physical function, and muscle strength in older adults living in residential care facilities. The findings support the application of Bot Fit to physical activity and functional gait training to improve age-related declines in physical function and muscle strength and to provide important insights into future robot-assisted exercise devices. Trial registration URL: https://register.clinicaltrials.gov/ . Unique identifier: NCT04610190 (10/26/2020).